2003
DOI: 10.1053/jhep.2003.50229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histologic Spectrum of Nonalcoholic Fatty Liver Disease Associated With Normal Alt Values

Abstract: A retrospective study was performed to (1) characterize the clinical and histologic features of those with nonalcoholic fatty liver disease (NAFLD) and normal alanine aminotransferase (ALT) values, (2) compare the spectrum of NAFLD associated with normal versus elevated ALT levels, and (3) determine whether there were differences in the clinical or histologic spectrum of NAFLD between those with a low normal versus high normal ALT value. A total of 51 subjects with NAFLD and normal ALT were identified and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
670
6
35

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,046 publications
(759 citation statements)
references
References 15 publications
48
670
6
35
Order By: Relevance
“…16,18 One possibility is that those were spurious results because of the use of inappropriate ALT cutoffs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,18 One possibility is that those were spurious results because of the use of inappropriate ALT cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…The length of liver samples was 18 AE 3 mm (median, 17; interquartile range, [16][17][18][19][20], and the number of portal tracts per sample was 7 AE 2 (median 6; interquartile range, 5-8). The ALT level had moderate correlation with steatosis grade (R = 0.32, P < 0.001), fibrosis stage (R = 0.20, P = 0.008) and the NAFLD activity score (R = 0.28, P < 0.001).…”
Section: Alanine Aminotransferase and Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recognised that ALT elevation is poorly correlated with the severity of histologic liver disease in chronic liver disease [24,25]. Mofrad et al [26] reported on a cohort of patients with normal ALT levels who were diagnosed as having NAFLD histologically and identified clinically (persistent hepatomegaly) or because the subjects were live liver transplant donors. There was no relation in this group between fibrosis stage (histologic) and ALT level.…”
Section: Specificity and Sensitivity Of The Lftmentioning
confidence: 99%
“…Although NAFLD has no specific clinical or laboratory features, a presumed diagnosis of NAFLD can often be made in a patient with a combination of a mildly elevated liver biochemistry, negative liver screen, ''bright'' liver on abdominal ultrasonography (USS), and the presence of metabolic risk factors such as hypertension, noninsulindependent diabetes mellitus and insulin-resistance, hyperlipidemia, and obesity [2][3][4]. The definitive diagnosis of NAFLD is made on a liver biopsy [5,6] as patients with NAFLD may present with ''normal'' liver biochemistry [7][8][9] and at least 20% of people with persistently abnormal alanine aminotransaminase values have an alternative diagnosis. More important, a liver biopsy is currently the only reliable method in distinguishing simple steatosis from NASH and allows an assessment of disease severity [5,6].…”
Section: Introductionmentioning
confidence: 99%